Dinamika Mazhab Pemikiran Ekonomi Islam Kontemporer: Integrasi Mazhab Iqtishādunā, Mainstream, dan Alternatif-Kritis dalam Kerangka Epistemologi dan Implementasi - Febri Kusuma (Multidisciplinary Journal of Religion and Social Sciences, 2026)
This study aims to analyze the differences and contributions of three schools of thought in Islamic economics—the Iqtishādunā School, the Mainstream School, and the Alternative-Critical School—and to formulate an integrative framework that can strengthen the development of contemporary Islamic economics. The research employs a qualitative approach through a literature review of primary works and academic sources. The analysis is conducted using a comparative-integrative method involving data reduction, thematic presentation, and conclusion drawing. The findings indicate that the Iqtishādunā School emphasizes normative sharia foundations and distributive justice; the Mainstream School strengthens institutional aspects through adaptation to modern economics; and the Alternative-Critical School highlights empirical evaluation of claims within Islamic economics. These three schools are complementary and cannot stand independently. This study proposes a triadic framework—sharia values, economic institutions, and scientific evaluation—as a novelty for building an Islamic economic paradigm that is more normative, operational, and evidence-based.